2015
DOI: 10.3109/00365521.2015.1046135
|View full text |Cite
|
Sign up to set email alerts
|

Physical fitness and physical activity in fatigued and non-fatigued inflammatory bowel disease patients

Abstract: Fatigued IBD patients show an impaired physical fitness and physical activity compared with non-fatigued IBD patients. This gives directions for a physical component in fatigue in IBD patients. Therefore, these new insights into fatigue indicate that these patients might benefit from an exercise program to improve physical fitness and physical activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
41
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 100 publications
1
41
1
Order By: Relevance
“…Evidence to date suggests that individuals with IBD should benefit from increased exercise [15,22,23,53,54], and in particular, that low-moderate intensity PA is safe [19,55]. The results from our study support these findings: no serious adverse effects related to exercise were reported.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Evidence to date suggests that individuals with IBD should benefit from increased exercise [15,22,23,53,54], and in particular, that low-moderate intensity PA is safe [19,55]. The results from our study support these findings: no serious adverse effects related to exercise were reported.…”
Section: Discussionsupporting
confidence: 82%
“…Low intensity exercise (cycling) was tolerated in patients with CD [17]; improvements in HRQOL and psychological benefits were reported in CD patients (with no/mild-moderate disease activity) undergoing low-moderate intensity PA programmes [16,18,19,20,21]. Greater impairments in physical fitness (assessed by cardiorespiratory fitness, 6-minute walk distance, and isokinetic muscle strength) and PA levels were reported in fatigued compared with non-fatigued IBD patients, and these were ameliorated by exercise [22]. Self-reported fatigue and skeletal muscle fatigue were significantly correlated in CD patients and non-IBD controls [23].…”
Section: Introductionmentioning
confidence: 99%
“…As known from research of other chronically ill people, PA can effectively address the symptoms of fatigue [65–67]. Fatigue contributes to a loss in muscle mass due to the lack of PA [23, 24, 68] especially in a population with an existing muscular disadvantaged [16]. Hitherto, the etiology of fatigue cannot be explained [65], though, an assessment of Cancer Related Fatigue (CRF) shows, that the amount of circulating pro-inflammatory blood cytokines are strongly associated with the severity of CRF [6971].…”
Section: Discussionmentioning
confidence: 99%
“…Abbreviations: IBDQ, Inflammatory Bowel Disease Questionnaire.intervention-based research on this topic 35. Observational studies have revealed fatigue to be negatively associated with physical activity, cardiorespiratory fitness and muscle strength;28,37 therefore, highlighting exercise as a candidate intervention. The current study provides support for a beneficial role of exercise by demonstrating that fatigue severity (IBD-F score) was an average of 2 points lower in the exercise group at 6 months (95% CI −4 to −1; P = 0.005).…”
mentioning
confidence: 99%